Kur’an-ı Kerim’de peygamberlerce tebliğ edilen temel dini esaslar - Albayrak, Kamil Ruhi (My University, 2006)
“Kur’an-ı Kerim’de Peygamberlerce Tebliğ Edilen Temel Dini Esaslar” adını taşıyan bu yüksek lisans tezinde, genelde tüm ilahi dinlerin, özelde İslam dininin Kur’an-ı Kerim’deki temel dini esasları araştırılmış ve sunulmuştur. Çalışma, giriş, üç ana bölüm ve sonuçtan oluşmaktadır. Girişte Kur’an-ı Kerim’e göre din kavramı sunulmuştur. Birinci bölümde Kur’an-ı Kerim’e göre dinin temel inanç esasları sunulmuştur. İkinci bölümde Kur’an-ı Kerim’e göre dinin temel ibadet esasları sunulmuştur. Üçüncü bölümde Kur’an-ı Kerim’e göre dinin temel davranış (ahlak) esasları sunulmuştur. Sonuç kısmında ise, araştırmada ulaşılan neticelere ve tezin genel değerlendirilmesine yer verilmiştir.

In this master thesis which is called “The Main Religious Basics that Conveyed by Prophets in The Qoran was studied and presented the main religious basics in The Qoran, in general, in all the divine religions, and particularly in Islam. The study includes the introduction, three main chapters, and the conclusion. In the Introduction, according to the Qoran the concept of religion is presented. In the chapter I, according to the Qoran the basic beliefs of the religion are presented. In the chapter II, according to the Qoran the basic worships of the religion are presented. In the chapter III, according to the Qoran the basic behaviors (transactions) of the religion are presented. The conclusions we reached in this thesis, and the general interpretation of the thesis are presented in Conclusion part.
Keywords: İslam Dini; Kur’an-ı Kerim_Dini Esaslar